Juridical Theoretical Study Of Granting And Abolition Services Of Encumbrance Rights That Eletronically Integrated - Arba Arba; Sudiarto Sudiarto; Rizky Yunian Sari (Faculty of Law, University of Mataram, 2022)
This study aims to examine and analyze the existence of an obligation that every granting and abolition of Encumbrance Rights (roya') must be registered, to examine and analyze the synchronization of legal arrangements for the implementation of registration of granting and abolition of Encumbrance Rights according to UUHT with the Ministry regulation of Agrarian Affairs & ATR Number 9 of 2019, As well as to study and analyze the legal consequences if the granting and abolition of Encumbrance Rights is not registered electronically. This type of research is normative legal research, with the approach method being a statutory approach, conceptual approach, and analytical approach. The results of the research are: 1) that each grant and abolition (roya) of the Encumbrance right must be registered, in accordance with the provisions that the granting and abolition of the Encumbrance must be registered as an absolute requirement and as a fulfillment of the publicity principle in the Law of Encumbrance Right. 2) In the Minister of Agrarian Affairs ATR BPN Number 19 of 2019 there are parts that are not in sync with the Law of Encumbrance Right, electronic documents that are not known in the UUHT and Roya can also be implemented without an agreement that these conditions are not in accordance with the provisions in the UUHT . 3) Legal Consequences If the granting of Encumbrance Rights is not registered, then in the provisions of the Encumbrance Right, the Encumbrance is never born/never existed. If the Encumbrance waranty is never born, then the creditor is not located as a priority creditor (separatist creditor) to get the debtor's debt to be repaid. Likewise, in the abolition of Encumbrance Right (roya), if it is not registered, the Encumbrance Right is considered to have never been erased, so that the waranty remains in the control of the creditor, and the loan agreement or principal agreement has not been paid off and ended. While for the Abolition Process (Roya) of Encumbrance Right as Maintenance of Land Registration Data, if the Encumbrance right certificate has been crossed out, then the land title certificate which is used as waranty for the Encumbrance will be returned to the debtor, while the Encumbrance Right certificate is withdrawn by the Land Office and declared no valid again, as well as the land books of Encumbrance Right is declared no longer valid.